Acute Effects of Liothyronine Administration on Cardiovascular System and Energy Metabolism in Healthy Volunteers - Chen, Shanshan; Wohlford, George F.; Vecchie’, Alessandra; Carbone, Salvatore; Yavuz, Sahzene; Van Tassell, Benjamin; Abbate, Antonio; Celi, Francesco S. (Frontiers in Endocrinology, 2022)
Context. The pharmacokinetics of liothyronine causes concerns for cardiovascular toxicity. While the effects of sustained increase in serum T3 concentrations are well described, little is known on the effects of acute changes in T3 concentrations due to rapid action of thyroid hormone. Objective. To assess the clinical relevance of transient increase of T3 levels on cardiovascular system and energy metabolism. Setting. Double-blind, three arms, placebo controlled, cross-over study (ClinicalTrials.gov Identifier: NCT03098433). Study Participants. Twelve volunteers (3 females, 9 males), age 27.7±5.1 years. Intervention. Oral administration of liothyronine 0.7 mcg/kg, equimolar dose of levothyroxine (0.86 mcg/kg), or placebo in three identical study visits. Blood samples for total T3, free T4 were collected at times 0’, 60’ 120’ 180’ 240’. Continuous recording of heart rate, blood pressure, and hemodynamic data was performed using the volume clamp method. Resting energy expenditure was measured by indirect calorimetry. An echocardiogram was performed on each study visit at baseline and after the last blood sampling. Main Outcome Measures. Changes in cardiovascular function and energy expenditure. Results. Following the administration of liothyronine, serum T3 reached a Cmax of 421 ± 57 ng/dL with an estimated Tmax of 120 ± 26 minutes. No differences between study arms were observed in heart rate, blood pressure, hemodynamics parameters, energy expenditure, and in echocardiogram parameters. Conclusions. The absence of measurable rapid effects on the cardiovascular system following a high dose of liothyronine supports the rationale to perform long-term studies to assess its safety and effectiveness in patients affected by hypothyroidism.